1997
DOI: 10.1097/00006676-199701000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Intraduodenal Free Fatty Acids Rather than Triglycerides Are Responsible for the Release of CCK in Humans

Abstract: Exocrine pancreas from different species behaves differently in response to the presence of intact or digested nutrients in the duodenum. A failure of cholecystokinin (CCK) release after a meal has been shown among patients with exocrine pancreatic insufficiency. This abnormality could be restored by the administration of pancreatic extracts, suggesting that digested rather than intact nutrients are responsible for the release of CCK and subsequently gallbladder contraction in humans. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…Most human studies, which have demonstrated an effect of ID lipid on CCK release, have used triglyceride emulsions, but recent work has clearly established that free fatty acids, rather than triglycerides, stimulate CCK secretion [10, 11]. In patients with pancreatic lipase insufficiency, the CCK response is reduced to triglycerides, but normal to oleic acid [10]; along the same line, administration of a lipase inhibitor [11] or application of non-absorbable fat in the form of polyester sucrose [12] prevents CCK release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most human studies, which have demonstrated an effect of ID lipid on CCK release, have used triglyceride emulsions, but recent work has clearly established that free fatty acids, rather than triglycerides, stimulate CCK secretion [10, 11]. In patients with pancreatic lipase insufficiency, the CCK response is reduced to triglycerides, but normal to oleic acid [10]; along the same line, administration of a lipase inhibitor [11] or application of non-absorbable fat in the form of polyester sucrose [12] prevents CCK release.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with pancreatic lipase insufficiency, the CCK response is reduced to triglycerides, but normal to oleic acid [10]; along the same line, administration of a lipase inhibitor [11] or application of non-absorbable fat in the form of polyester sucrose [12] prevents CCK release.…”
Section: Introductionmentioning
confidence: 99%
“…While there are trypsin-sensitive CCK-releasing peptides which may mediate the effect of dietary protein (Liddle, 1995), the precise mechanism for lipids is unknown. Dietary lipids stimulate CCK secretion specifically via intraduodenal free fatty acids (Beardshall et al 1989;Guimbaud et al 1997). Although it is known that long chain triglycerides but not medium chain triglycerides stimulate release of CCK in humans (Isaacs et al 1987), the precise structural specificity of the CCK response to luminal fatty acids has not been characterized.…”
mentioning
confidence: 99%
“…The degree of unsaturation of the dietary fat can influence the secretion and function of hormones and enzymes (Shall et al, 1989;Guimbaud et al, 1997), and digestibility (Zollitsch et al, 1997). Therefore, growth hormones might be linked with the dietary fat and fatty acids in case of broilers.…”
Section: Growth Performance Of Birdsmentioning
confidence: 99%